Effects of oral clonidine on bleeding in pelvic and acetabular fractures surgery: a randomized controlled trial - Mohamad Qoreishy; Alireza Mirahmadi; Mohammad Movahedinia; Sohrab Keyhani; Arash Maleki; Bahram Naghibi (BMC Musculoskeletal Disorders)
Abstract Background High blood loss results in major complications in pelvic and acetabular surgeries. Decrement of blood loss during and after surgery reduces morbidity and mortality of the patients. Clonidine is an antihypertensive alpha-2 agonist that has been shown to reduce blood loss in different surgeries. This study aims to evaluate the effects of preoperative oral administration of clonidine in patients who underwent surgery for pelvic and acetabulum fractures. Methods A randomized, triple-blinded clinical trial was conducted on 88 patients (79 men and 9 women) scheduled for pelvic or acetabular fracture surgery. Patients were divided into two groups. The intervention group received 200 mcg of oral clonidine 75 to 90 min before anesthesia. Control groups received a placebo with a similar color and shape to clonidine. We compared two groups regarding the blood loss volume, postoperative pain, quality of the surgical visual field, and day one and three postoperative hemoglobin levels. Results Postoperation hemoglobin level was significantly dropped in both groups (P < 0.05). Post-surgery, the hemoglobin level difference between the groups increased and became significant by day three (9.8 ± 1.2 Vs. 8.4 ± 1.2, P = 0.02). The number of patients who required postoperative blood transfusion in the intervention group was less than in the control group (3 vs. 10, P = 0.03). Preoperative clonidine significantly reduced postoperation pain and improved the quality of the surgeon’s visual field (P < 0.001). Conclusions Preoperative oral clonidine administration reduced blood loss and the number of postoperative transfusion units in pelvic and acetabular fracture surgeries. In addition, it improved the surgeon’s visual field quality and reduced postoperative pain.